MEDIA PEMBELAJARAN INTERAKTIF WORD WALL TERHADAP HASIL BELAJAR SISWA PADA MATERI ETIKA PROFESI KELAS X AKUNTANSI SMK PARIWISATA KOSGORO KOTA CIREBON - Kurnia, Maya Dewi; Febianti, Yopi Nisa; Ambarwati, Ambarwati (Universitas Tanjungpura, 2024)
Word wall learning media is an interactive e-learning learning media used by teachers to improve student learning outcomes during classroom learning. Word wall media in the form of core learning concepts equipped with pictures, diagrams or real objects. The word wall learning media is applied to the Professional Ethics material for class X Accounting at the Kosgoro Tourism Vocational School, Cirebon. It is expected to help improve student learning outcomes. This article is written using a quantitative method in the form of a Pre-Experimental Design with a One Group Pretest-Posttest Design research design. Through a prioritized approach with pre-test data to measure students' cognitive abilities, then given a word wall learning media treatment, taking post-test data to measure students' final abilities. Data were analyzed with descriptive statistics of proportions and t-test using SPSS. The results of the analysis can be concluded that word wall interactive learning media in this study has increased. The results of the data from the t test were rejected because the class sample used in this study was very small so it was not suitable as an interactive medium.Keywords: Learning Media, Wordwall and Learning Outcomes. AbstrakMedia pembelajaran word wall merupakan media pembelajaran e-learning interaktif yang digunakan guru dalam meningkakan hasil belajar siswa selama pembelajaran dikelas. Media Word wall berupa konsep inti pembelajaran dilengkapi gambar, diagram, atau objek nyata. Media pembelajaran word wall diterapkan pada materi Etika Profesi kelas X Akuntansi di SMK Pariwisata Kosgoro, Cirebon. Diharapkan dapat membantu meningkatkan hasil belajar siswa. Penelitian ini menggunakan metode kuantitatif dalam bentuk Pre Experimental Design dengan desain penelitian One Group Pretest-Posttest Desaign. Melalui pendekatan diawali dengan data pre-test untuk mengukur kemampuan kognitif peserta didik, kemudian diberikan perlakuan media pembelajaran word wall, diambil data post-test untuk mengukur kemampuan akhir siswa. Data dianalisis dengan statistik deskriptif persentase dan uji-t menggunakan SPSS. Hasil data dari uji t Ho ditolak karena sampel kelas yang digunakan pada penelitian ini sangat sedikit sehingga kurang cocok sebagai media interaktif.Kata Kunci: Media Pembelajaran, Wordwall dan Hasil Belajar.